Caracterização Química e Avaliação da Atividade Gastroprotetora de Extratos do Agaricus brasiliensis - Câmara Neto, João Francisco (2019)
In the contemporary scenario, about 4 million people a year are affected by peptic ulcer worldwide, which is a serious public health problem. In recent years, extracts from the mushroom Agaricus brasiliensis have become increasingly popular due to its long history for treating diseases due to its anticancer, immunomodulatory, anti-inflammatory, antitumor, antiviral and antioxidant properties. Thus, this work aims to study extracts from the mushroom A. brasiliensis, regarding their chemical composition and biological activities in vitro and in vivo, in order to evaluate their gastroprotective activity. Three extracts of the mushroom were prepared, one hydroalcoholic (70%) (EEAb), the other aqueous containing (EAAb) or not (EASP) the mushroom polysaccharides. These were carried out to identify the main classes of secondary metabolites (qualitatively, putatively and structurally), chemical composition, quantification of the major compound, as well as the levels of phenolic compounds, and put an end to the evaluation of antioxidant activity. Furthermore, for the most promising extract (through the results obtained for the aforementioned analyses) its gastroprotective effect and possible ways of action were evaluated. The yields obtained for the extracts were 53.53% (EEAb), 54.08% (EAAb) and 51.50% (EASP), guaranteeing them the presence of several classes of secondary metabolites, such as alkaloids, catechins, coumarins, free steroids, phenols, flavonoids, resins, saponins and xanthones (qualitatively). The quantification of CHNS-O by elemental analysis proved to be very similar for the extracts, with slight variations in sulfur and oxygen contents. Among the many compounds putatively identified by Ultra Efficiency Liquid Chromatography (UPLC-QTOF-MSE) stand out the presence of mannitol, malic acid, pyroglutamic acid, L-agaritin and L-valine. From the results of the spectra of the analyzes performed by Nuclear Magnetic Resonance (NMR) spectroscopy, intense signals similar to those of mannitol were observed, confirmed later also by the analysis of the mannitol pattern in the thin layer chromatography (TCD) technique for the extracts. The quantification of mannitol by High Performance Liquid Chromatography (HPLC) in the extracts obtained levels of 40.81 ± 0.74%, 31.25 ± 1.25% and 73.10 ± 0.24% for EEAb, EAAb and EASP, respectively. Regarding the contents of total phenols (mg EAG/g) and flavonoids (mg EQ/g) for the extracts, 89.23 ± 2.56 and 14.33 ± 0.07 for EEAb, 60.17 ± 3 .92 and 9.37 ± 0.18 for the EAAb and 55.04 ± 1.48 and 8.11 ± 0.18 for the EASP, respectively. These results corroborate the good antioxidant activities in terms of efficient concentration (EC50) for the extracts, being 117.04 ± 0.76 μg mL-1, 156.95 ± 4.80 μg mL-1 and 290.98 ± 6 .77 μg mL-1 for EEAb, EAAb and EASP, respectively. For the ferrous ion chelation capacity (μg mL-1) results, 619.25 ± 1.59 were obtained for EEAb, 675.14 ± 1.82 for EAAb and 2206.45 ± 14.07 for EASP, respectively. Due to the most promising results, the EEAb was chosen to proceed with the bioguided study for the gastric ulcer test (at doses of 5, 25 and 50 mg kg-1), as well as to evaluate the possible routes of action. EEAb at doses of 25 and 50 mg kg-1 showed a good gastroprotective response in the model of gastric ulcer induced by absolute ethanol. The dose of 25 mg kg-1 of EEAb was chosen for the study of the pathways, which showed modulation/action on the nitric oxide (NO) and prostaglandin pathways. Thus, it is concluded that EEAb presented gastroprotective activity by reducing oxidative stress, reducing histopathological parameters and decreasing mastocytosis, due to its secondary metabolites acting in the nitric oxide (vasodilation) and prostaglandins (mucus and bicarbonate production) pathways.